Intermittent fasting boosts antitumor immunity by restricting CD11b+Ly6Clow Ly6Glow cell viability through glucose metabolism in murine breast tumor model - Chenghao Fu; Zhehao Liang; Zemiao Niu; Ning Chen; Yuemin Li; Zhenhua Liang; Yanwei Huo; Hao Xi; Rong Wang; Yonghuan Yan; Xiaoru Gano; Mengtian Wang; et al. (Food Science and Human Wellness)
Intermittent fasting can benefit breast cancer patients undergoing chemotherapy or immunotherapy. However, it is still uncertain how to select immunotherapy drugs to combine with intermittent fasting. Herein we observed that two cycles of fasting treatment significantly inhibited breast tumor growth and lung tissue metastasis, as well as prolonged overall survival in mice bearing 4T1 and 4T07 breast cancer. During this process, both the immunosuppressive monocytic- (M-) and granulocytic- (G-) myeloid-derived suppressor cell (MDSC) decreased, accompanied by an increase in interleukin (IL) 7R+ and granzyme B+ T cells in the tumor microenvironment. Interestingly, we observed that Ly6Glow G-MDSC sharply decreased after fasting treatment, and the cell surface markers and protein mass spectrometry data showed potential therapeutic targets. Mechanistic investigation revealed that glucose metabolism restriction suppressed the splenic granulocyte-monocyte progenitor and the generation of colony-stimulating factors and IL-6, which both contributed to the accumulation of G-MDSC. On the other hand, glucose metabolism restriction can directly induce the apoptosis of Ly6Glow G-MDSC, but not Ly6Ghigh subsets. In summary, these results suggest that glucose metabolism restriction induced by fasting treatment attenuates the immune-suppressive milieu and enhances the activation of CD3+ T cells, providing potential solutions for enhancing immune-based cancer interventions.